Spat efficiency of the smooth scallop Flexopecten glaber in the Aegean Sea, Türkiye - Yigitkurt Selcuk; Kırtık Ali; Kurtay Evrim; Ugur Sinem; Durmaz Yasar (Oceanological and Hydrobiological Studies)
This study was carried out to determine the spat efficiency of the smooth scallop Flexopecten glaber (Linnaeus) in surface and bottom water at the Ozbek coast (Türkiye) of the Aegean Sea from September 2017 to August 2018. The environmental parameters (temperature, salinity, chlorophyll-a, and total particulate matter) were also monitored at two depths. The average water temperature at the surface and bottom were 19.79 ± 5.62°C and 19.73 ± 5.24°C, respectively. The lowest chlorophyll-a values were recorded in February (1.12 g l−1) and June (1.23 μg l−1) at the surface and bottom, respectively. The highest chlorophyll-a value was recorded in August at both depths. Throughout the study, the number of F. glaber on the collectors was 270.33 ± 43.54 spat m−2 and 145.66 ± 18.03 spat m−2 were detected on the bottom collectors. A statistically significant difference was found between the growth of the spat attached to the surface and bottom collectors (p < 0.05).